THE SIGNIFICANCE OF LEARNING STYLES AND LANGUAGE LEARNING STRATEGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is intended to give basic information about learning styles and language learning strategies in language acquisition. Also, this paper is based on analyses some features and categories of learning styles in language learning process. As we know, Learning strategies are steps taken by learners to enhance their learning. An active use of language learning strategies helps learners in control of their own learning by developing language skills, increasing confidence and motivation in learning process.